Estate as risk developer: the Ecuadorian case - Cajas, Lorena (2013)
The present article pursues to analyze the different levels of responsibility of the various social actors and especially the Ecuadorian Estate, as one of them, in the process of generating vulnerabilities in Ecuador. Additionally, and derived from this analysis this article proposes some fundamental elements for the implementation of an appropriate risk management from the Ecuadorian Estate. As far as we know these elements are: citizen participation, government ?s role as a public founds administrator, actual legal regulations, transversal impact of a disaster and due to it, the necessity to implement risk management considerations as transversal variables; the structure of the Estate from an institutional approach and information as a key social driver.